2013
DOI: 10.1371/journal.pone.0079499
|View full text |Cite
|
Sign up to set email alerts
|

DNA, Cell Wall and General Oxidative Damage Underlie the Tellurite/Cefotaxime Synergistic Effect in Escherichia coli

Abstract: The constant emergence of antibiotic multi-resistant pathogens is a concern worldwide. An alternative for bacterial treatment using nM concentrations of tellurite was recently proposed to boost antibiotic-toxicity and a synergistic effect of tellurite/cefotaxime (CTX) was described. In this work, the molecular mechanism underlying this phenomenon is proposed. Global changes of the transcriptional profile of Escherichia coli exposed to tellurite/CTX were determined by DNA microarrays. Induction of a number of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 44 publications
4
13
0
Order By: Relevance
“…As mentioned, controversial evidence has been shown indicating that bactericidal antibiotics owe part of their toxicity to oxidative stress establishment [ 33 , 34 ]. Notably, the colonization phenotype is not a consequence of bacterial adaptation to the oxidative damage generated by the antibiotic ( figure 4 ), as has been shown previously [ 32 ].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…As mentioned, controversial evidence has been shown indicating that bactericidal antibiotics owe part of their toxicity to oxidative stress establishment [ 33 , 34 ]. Notably, the colonization phenotype is not a consequence of bacterial adaptation to the oxidative damage generated by the antibiotic ( figure 4 ), as has been shown previously [ 32 ].…”
Section: Discussionsupporting
confidence: 71%
“…On the other hand, it has been described that bactericidal antibiotics, and specifically CTX, generate oxidative stress [ 32 34 ]. However, this concept remains controversial as many publications have challenged the original findings [ 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…bacteria, including resistant strains, persisters, and biofilms. With respect to tellurite, two recent studies by Molina-Quiroz et al (140,141) found that nonlethal levels of this tellurium oxyanion can enhance the lethality of several antibiotics, including ampicillin and gentamicin. They demonstrated that a ROS component is involved in the lethal synergy of cefotaxime (a cephalosporin β-lactam) with tellurite by showing that the combination treatment results in oxidative damage to DNA and proteins (141).…”
Section: Cell Deathmentioning
confidence: 99%
“…UPEC cultures were grown as described above and challenged for 1 h with ampicillin at 1,250 µg/ml or with 50 µM FeSO 4 and 10 mM H 2 O 2 to generate hydroxyl radicals by the Fenton reaction (positive control) as previously described ( 32 ). Total ROS and hydroxyl radical levels were assessed with H 2 DCFDA and HPF, respectively, as previously described ( 14 , 53 ). Fluorescence of cultures was determined in a Synergy H1 microplate reader (BioTek) fluorimeter.…”
Section: Observationmentioning
confidence: 99%